PENERAPAN KODE ETIK JURNALISTIK KAITANNYA DENGAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG PERS PADA KEBEBASAN PERS - Lestari Made Novita Dwi (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2017)
Indonesian ensure everyone has an equal footing in the law (equality before the law). This is confirmed in the  state constitution that says that  Indonesia is  a constitutional state  (recht state) and is run entirely under the Act. Print mass media is one means to meet the public’s right to know and develop public opinion, with appropriate information menyamaikan, accurate and true. the  role  of journalists is very important in meeting the  right  people  and  at the time of carrying out the work or the profession was certainly should get legal protection, as stated in article 8 of the law number 40 of 1999 concerning the press. Where once journalists desperately need legal protection from work so when the duty was not being chased or overshadowed by the fear of threat, terror, and violence. The form of legal safeguards provided by the print media company to journalists is to the existence of the attorneys for the law of rock journalists accompany the  affected  cases was  accompanied  at the time either in  court  or  outside the  court. But in addition to providing legal protection for journalists, there is no sanction against journalists who carried stories that do not fit as well as a breach of journalistic ethics. Keywords: Legal Protection, Journalists and Journalistic Ethics